2005
DOI: 10.1080/10485250500337138
|View full text |Cite
|
Sign up to set email alerts
|

Non-parametric hazard function estimation using the Kaplan–Meier estimator

Abstract: Estimation of the hazard function when the data are censored is an important problem in medical research. In this article, we propose a simple non-parametric estimator of the hazard function. Its asymptotic properties are derived, and numerical comparisons with other existing estimators are made. The proposed estimator is shown to be at least as good as the other estimators from both the theoretical and the numerical points of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…from which we may considerλ n (t|x) as a local linear-type extension to conditional hazard function of the estimator suggested by Kim et al (2005).…”
Section: Proposed Estimatormentioning
confidence: 99%
See 4 more Smart Citations
“…from which we may considerλ n (t|x) as a local linear-type extension to conditional hazard function of the estimator suggested by Kim et al (2005).…”
Section: Proposed Estimatormentioning
confidence: 99%
“…In fact, they applied kernel method to both the response and the covariates, and used a local polynomial regression method in estimation. On the other hand, Kim et al (2005) suggested a nonparametric estimation of unconditional hazard function using the Kaplan-Meier estimator (cf. Kaplan & Meier, 1958).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations